Electrochemical characterization of three types of Co-Cr based alloys manufactured by casting and selective laser melting according to ISO 10271. Issue 7 (July 2022) - Al Jabbari, Youssef S.; Karavoltsos, Sotiris; Kokkinos, Christos; Polychronis, Georgios; Economou, Anastasios; Zinelis, Spiros
Abstract: Objective: To characterize the effect of elemental composition and manufacturing process on the electrochemical properties of Co-Cr-Mo, Co-Cr-W and Co-Cr-Mo-W alloys. Methods: Six Co-Cr based alloys were included in this study. All alloys are Co-Cr based alloys, classified in three different types according to their elemental composition. The first group has Mo as the third alloying element while the second one has W instead of Mo. The third one has both alloying elements. The groups are further divided by the manufacturing process (casting or Selective Laser Melting(SLM)). All groups were subjected to static immersion, open circuit potential, anodic scan, SEM/EDX analysis, static and cyclic tarnish testing according to ISO 10271 requirements. The ionic release was evaluated by inductively coupled plasma mass spectrometry and the results were statistically analyzed by two way ANOVA and Tukey test (a=0.05). Results: No statistical differences were identified for Co-Cr-Mo alloy for all elements and their total ionic release between casting and SLM manufacturing processes, in contrast to significantly lower values for SLM groups for the other two groups. All groups tested demonstrated similar performance in OCP and AS testing while no gross elemental changes before and after AS were identified following EDX analysis. All alloys fulfilled the requirements of tarnish resistance Conclusions: The ionic release is dependent on alloy type and manufacturing process while all groups were found to fulfill the requirements of international standards for ionic release, corrosion and tarnish resistance and thus an acceptable clinical performance is anticipated.